OPTIMALISASI KINERJA GURU SD: PERAN INSENTIF DAN KEPUASAN KERJA DALAM MENINGKATKAN KUALITAS PENDIDIKAN - DARMAWATI DARMAWATI (JURNAL ILMIAH SIMANTEK, 2023)
In 2018-2022 the number of primary school teachers in Indonesia tends to decrease. This is caused by the declining performance of some teachers which makes some of these teachers no longer have the enthusiasm to continue their profession as elementary school teachers, where this situation is influenced by the provision of incentives that are not in accordance with the tasks that have been carried out and the organizational climate of the school which is not good and tends to disrupt the teaching and learning process, as a result, this declining performance will have an impact on decreasing job satisfaction which makes the commitment to continue educating elementary school students aged 6-12 years fade. The purpose of this study is to know and analyze the extent to which the variables of incentive provision and organizational climate both partially and simultaneously affect the performance variables of elementary school teachers in Indonesia through the variables of job satisfaction and work commitment of elementary school teachers in Indonesia as intervening variables. The population of this study is elementary school teachers throughout Indonesia, totaling 1,460,000 people, while the sampling method is to use the accidental sampling method, where the number of samples available after being calculated using the Slovin formula is 51 people. The data analysis used is using the structural equation model (SEM) method. The results of the study explain that partially only the incentive provision variable affects the performance of elementary school teachers in Indonesia, the incentive provision variable also affects the job satisfaction of elementary school teachers in Indonesia, as well as the work commitment variable of elementary school teachers in Indonesia. Simultaneously, only the variable of incentive provision affects the performance variable of elementary school teachers in Indonesia through the variable of job satisfaction and work commitment as an intervening variable, where the incentives provided will encourage teachers to continue to develop themselves, and be able to improve the ability, capacity and capability of teachers, so that their performance is lifted, as well as increasing job satisfaction and elementary school teachers in Indonesia will continue to be committed to continuing to educate children aged 6-12 years to become more developed and their knowledge can be developed and used in society.